EVALUATION OF CLIMATE SCENARIOS PROJECTIONS AND ASSOCIATED ERRORS IN A REGION IN ILLINOIS (USA) ACCORDING TO CMIP5 MODELS - Resende, Nicole Costa; Miranda, Jarbas Honorio (Revista Brasileira de Climatologia, 2021)
Observed data from different parts of the world shows that many natural systems are being affected by regional climate changes. Some models has been used as a tool to help studies to evaluate the impacts of climate changes in different sectors.However, this models has some errors due to the parametrization necessary in this models and also due to the streamline equations in order to describe a chaotic system. This issue make essential to conduct research in order to verify the regions where these errors are more prominent. The aim of this research is evaluate the climate scenarios given by CMIP5 models by studying the associated errors of this modeling. Also, is described the climatology and the possible changes of climate and extreme events in the region according to different scenarios of projections. The model IPSL(CM5MR) was founded as the most accurate for the analyzed region, although the model presented tendency of underestimation of precipitation and average and maximum temperature between 1901 to 2005. Regarding to minimum temperature this models has tendency to overestimation. Regarding to the indexes of extreme events, we noticed that most of them showed good performance. The model shows tendency of increasing of precipitation and increase of occurrence of extreme events, mostly of accumulated precipitation in one and 5 days. Consecutive wet days also may increase. It is also noticed decreasing of number of frost days and icing day and increasing of number of summer days.